La question de l'égalité des parcours en faculté de médecine : les conditions d'entrée à l'université des nouvelles carabines - Céline Avenel (Presses universitaires de la Méditerranée, 2012)
A mass access for women to medical studies was encouraged in these last twenty years from first-year medical studies to postgraduate medical studies. The girls became the clear majority (64 %) amongst the first-year students in 2002 (Hérault et Labarthe, 2003). This present mass feminization represents a real historical change. We propose a social and gendered analyze of this feminization, a major development in higher education in France, in light of two principles : that of equality in career in medical studies and that of gender equality. Which can be the incidences of a mass movement in terms of carrer for future medical students ? Does this feminization participate in an equality of access to the medical studies, in terms of social origins ?